Russia: Turn to China? - Margarete Klein; Kirsten Westphal (Stiftung Wissenschaft und Politik (SWP), 2016)
After its relations with the West deteriorated massively in the course of the Ukraine crisis, Russia has been aligning itself increasingly towards China. This shift is most obvious in the strategic spheres of military and energy cooperation. Even if the immediate impacts on Germany and the European Union - caused by the dynamics in the relationship between these two major neighbours in the East - are limited, the development is of great relevance for international relations and the global order. It would therefore be wrong to underestimate the long-term ramifications. Germany and the European Union should counterbalance these nascent tectonic shifts with inclusive and multilateral cooperation and dialogue initiatives in the Euro-Asian region. Regional and global cooperation should be shaped by economic exchange, infrastructure expansion and the search for solutions to global problems. (SWP Comments)
Keywords: 320